2021
DOI: 10.3390/ijms22189690
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransducive Biomimetic Systems for Chondrogenic Differentiation In Vitro

Abstract: Osteoarthritis (OA) is a long-term chronic joint disease characterized by the deterioration of bones and cartilage, which results in rubbing of bones which causes joint stiffness, pain, and restriction of movement. Tissue engineering strategies for repairing damaged and diseased cartilage tissue have been widely studied with various types of stem cells, chondrocytes, and extracellular matrices being on the lead of new discoveries. The application of natural or synthetic compound-based scaffolds for the improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 141 publications
(174 reference statements)
0
24
0
Order By: Relevance
“…A variety of biological factors and physiochemical cues have been reported for their influences on the functions and differentiation of stem cells [ 34 , 35 , 36 , 37 ]. Supplementation with CI factors such as dexamethasone and TGF-β3 is important for chondrogenic differentiation of stem cells [ 38 , 39 , 40 ]. Induction factors are generally added to the culture medium during in vitro induction culture.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of biological factors and physiochemical cues have been reported for their influences on the functions and differentiation of stem cells [ 34 , 35 , 36 , 37 ]. Supplementation with CI factors such as dexamethasone and TGF-β3 is important for chondrogenic differentiation of stem cells [ 38 , 39 , 40 ]. Induction factors are generally added to the culture medium during in vitro induction culture.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that mechanical forces induce the differentiation and maturation of stem cells toward bone 4,24,25 and cartilage cells 11,[26][27][28] . Laminar shear stress mediates early lineage specification of singlecell monolayer-cultured mouse ES cells 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion rate of solutes, enzymes, factors, and other elements in the hydrogel depends on the relationship between the size of the molecule/particle and the mesh size of the polymer network [ 118 , 120 ]. Thus, the hydrogel porosity, which is related to its mechanical and physicochemical properties (swelling ratio, degradation resistance), influences the degradability rate of the hydrogel [ 121 , 122 ], nutrient diffusion, transport of oxygen, removal of toxic components, as well as the cell proliferation, migration, and adhesion [ 3 , 41 , 121 , 122 , 123 ]. Therefore, by modulating the mesh size, swelling, and degradability rate, it is possible to produce hydrogels capable of stabilizing molecules and other bioactive factors and releasing them in a controlled manner, enhancing and tuning the regenerative process.…”
Section: Hydrogel and Cartilage Regenerationmentioning
confidence: 99%
“…Moreover, transduction of mechanical stimuli (i.e., mechanotransduction) in chondrocytes influences their maintenance, viability, gene expression, chondrogenic activity, and ECM deposition [ 3 ]. Under normal conditions, the few chondrocytes present in cartilage can maintain the composition of the ECM in a balance between degradation and production of ECM proteins.…”
Section: Introductionmentioning
confidence: 99%